1984
DOI: 10.1021/ic00173a021
|View full text |Cite
|
Sign up to set email alerts
|

NMR studies of thermochromic transitions in copper(II) and nickel(II) complexes with N,N-diethylethylenediamine

Abstract: The temperature dependence of the proton and 19F NMR spectra of bis(7V,/V-diethylethylenediamine)copper(II) perchlorate, bis(7V,JV-diethylethylenediamine)copper(II) tetrafluoroborate, bis(7V,jV-diethylethylenediamine)nickel(II) perchlorate, and bis(lV,7V-diethylethylenediamine)nickel(II) tetrafluoroborate were studied. The second moments of the spectra show a sharp decrease at the temperature of the thermochromic phase transition. This decrease is due to the onset of dynamic motion in the ligand molecule. A mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This mechanism seems to be consistent with various experimental results so far available. However, the relationship between the microscopic aspects hitherto reported and the macroscopic energetic and entropic aspects was still unclear.…”
Section: 3 Enthalpy Change Due To Thermochromismmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism seems to be consistent with various experimental results so far available. However, the relationship between the microscopic aspects hitherto reported and the macroscopic energetic and entropic aspects was still unclear.…”
Section: 3 Enthalpy Change Due To Thermochromismmentioning
confidence: 99%
“…This mechanism seems to be consistent with various experimental results so far available. However, the relationship between the microscopic aspects [444][445][446][447][448] hitherto reported and the macroscopic energetic and entropic aspects was still unclear. Nishimori et al measured heat capacities of [Cu(dieten) 2 ]-X 2 by adiabatic calorimetry.…”
Section: Enthalpy Change Due To Thermochromismmentioning
confidence: 99%
“…This mechanism seems to be consistent with various experimental results so far available. However, the relationship between the microscopic aspects (116)(117)(118)(119)(120) hitherto reported and the macroscopic energetic and entropic aspects was still unclear.…”
Section: Thermochromic Phase Transitionsmentioning
confidence: 99%
“…Copper(II) and nickel(II) complexes with the bidentate diamine ligand were studied extensively due to their thermochromic properties [7][8][9][10][11][12][13][14][15]. The investigations revealed that the nature of the diamine ligand and counter anion are crucial for the thermochromism.…”
Section: Introductionmentioning
confidence: 99%